2005
DOI: 10.1016/s0007-8506(07)60110-3
|View full text |Cite
|
Sign up to set email alerts
|

Pad Surface Roughness and Slurry Particle Size Distribution Effects on Material Removal Rate in Chemical Mechanical Planarization

Abstract: The ability to predict material removal rates in chemical mechanical planarization (CMP) is an essential ingredient for low cost, high quality IC chips. Recently, models that address the slurry particles have been proposed. We address three such models. The first two differ only in how the number of active particles is computed. Both assume that pad asperities are identical and nonrandom. The third is dynamic in accommodating changing pad properties. For larger mean particle size (diameter), the role of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 14 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…Wang et al [29] extended the model to include inelastic contact between pad asperity and wafer surface. They also incorporated the effect of abrasive particles on the material removal rate decay [30]. The model correctly predicted the MRR decay trend that matches the experimental results.…”
Section: Pad Conditioning and Its Effect On Cmp Performancementioning
confidence: 61%
See 1 more Smart Citation
“…Wang et al [29] extended the model to include inelastic contact between pad asperity and wafer surface. They also incorporated the effect of abrasive particles on the material removal rate decay [30]. The model correctly predicted the MRR decay trend that matches the experimental results.…”
Section: Pad Conditioning and Its Effect On Cmp Performancementioning
confidence: 61%
“…They showed that with this modification and careful selection of pad surface roughness parameters (asperity height distribution PDF), the time-varying (dynamic) MRR model can have significant potential in the prediction of MRR and MRR decay. They further presented another model incorporating the abrasive particle effects and considered that material removal comes from the interaction of the wafer and the active particles entrapped in the pad asperity-wafer contact areas [30]. This model reflects not only the effects of pad properties such as Young's modulus, hardness, asperity density, tip curvature, and height distribution but also the effects of abrasive particle (mean) size and size distribution on the polishing removal rate at a given polishing time.…”
Section: Review Of Modeling Of Pad Effects On Polishing Performancementioning
confidence: 99%
“…Similarly, from (19), (20), and (25), the relation between the nominal pressure, p, and the separation distance, d, can be estimated by…”
Section: A Contact Area Ratiomentioning
confidence: 99%
“…Some researchers [20], [21] have investigated the number of active particles, whereas others [22], [23] have conducted some experimental studies on the contact ratio of the pad asperities. Based on these studies, it can be predicted that the effective particle number is more than 1,000,000.…”
Section: Kinematic Optimization Based On Trajectorymentioning
confidence: 99%